Quantum‐resistant authentication algorithms for satellite‐based augmentation systems. Issue 1 (17th February 2019) - Neish, Andrew; Walter, Todd; Enge, Per
Abstract: Cryptography in the form of digital signatures can be part of the solution to the threat of spoofing and is going to be implemented on Galileo and other Global Navigation Satellite Systems. Digital signatures incorporated into the data stream authenticate the integrity of the data as well as the origin of the message. Implementing a digital signature on a satellite‐based augmentation system for use in aviation will require the signature to be short and the signing procedure to be cryptographically relevant for the next 30 or more years. With the advent of quantum computing, many state‐of‐the‐art authentication schemes are no longer viable, so an authentication scheme implemented in satellite‐based augmentation system will need to be quantum secure. This paper introduces the cryptographic primitives (foundational problems) necessary to understand the vulnerabilities in modern‐day cryptography due to quantum computing and investigates the use of TESLA (Timed Efficient Stream Loss‐tolerant Algorithm) and EC‐Schnorr (Elliptic Curve‐Schnorr) algorithms in broadcast systems.